1991
DOI: 10.1126/science.1646484
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Heparan Sulfate for bFGF-Mediated Fibroblast Growth and Myoblast Differentiation

Abstract: Basic fibroblast growth factor (bFGF) binds to heparan sulfate proteoglycans at the cell surface and to receptors with tyrosine kinase activity. Prevention of binding between cell surface heparan sulfate and bFGF (i) substantially reduces binding of fibroblast growth factor to its cell-surface receptors, (ii) blocks the ability of bFGF to support the growth of Swiss 3T3 fibroblasts, and (iii) induces terminal differentiation of MM14 skeletal muscle cells, which is normally repressed by fibroblast growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
968
3
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,460 publications
(1,005 citation statements)
references
References 35 publications
28
968
3
6
Order By: Relevance
“…Additionally, FHFs and FGFs are similar in their affinity for heparin, which has aided in FHF protein purification (Olsen et al, 2003). While FGFs utilize extracellular heparan sulfate proteoglycan (HSPG) as an integral cofactor in receptor clustering (Rapraeger et al, 1991;Schlessinger et al, 2000;Yayon et al, 1991), FHFs reside in an intracellular environment lacking HSPGs. FHFs have conserved the heparin-binding domain for use in binding one of its protein targets (see below).…”
Section: Vertebrate Fhf Gene Expression and Protein Distributionmentioning
confidence: 99%
“…Additionally, FHFs and FGFs are similar in their affinity for heparin, which has aided in FHF protein purification (Olsen et al, 2003). While FGFs utilize extracellular heparan sulfate proteoglycan (HSPG) as an integral cofactor in receptor clustering (Rapraeger et al, 1991;Schlessinger et al, 2000;Yayon et al, 1991), FHFs reside in an intracellular environment lacking HSPGs. FHFs have conserved the heparin-binding domain for use in binding one of its protein targets (see below).…”
Section: Vertebrate Fhf Gene Expression and Protein Distributionmentioning
confidence: 99%
“…The importance of cell-surface heparan sulphate in the activation of signalling receptors by growth factors was first suggested in studies which showed that a loss of cell-surface heparan sulphate, caused either by treatment with a metabolic inhibitor of heparan sulphate synthesis (sodium chlorate) [90] or mutation of a gene coding for an enzyme of heparan sulphate biosynthesis [91], resulted in the failure of bFGF to bind and activate the FGF-receptor kinase under the experimental conditions used. Many subsequent studies have confirmed these initial observations and have extended them to include other heparan sulphate-binding growth factors [84,85,88].…”
Section: Modulation Of Growth-factor-receptor Activationmentioning
confidence: 99%
“…TC-32 cells were grown in low serum conditions (0.5% FCS in RPMI 1640 media) for 24 h, and then treated with either aFGF (0.1, 1 or 10 ng ml À1 ) or bFGF (0.1, 1 or 10 ng ml À1 ) in low serum media containing heparin (10 U ml À1 ) for up to 30 min at 371C. Heparin was included in conditions for FGF treatment as its molecular association with FGF and its receptors is reported to be essential for biological activity (Rapraeger et al, 1991;Lin et al, 1999). Flasks were placed in ice, cells were washed in cold PBS and lysates were prepared in lysis buffer (50 mM HEPES (pH 7.5), 100 mM NaCl, 1 mM EGTA, 1 mM DTT, 10 mM MgCl 2 , 1% (v v À1 ) Triton X-100, 10 mg ml À1 aprotinin, 10 mg ml À1 leupeptin, 1 mM sodium orthovanadate (Sigma), 25 mM sodium fluoride (Sigma)).…”
Section: Activation Of Fgfr3 and Fgfr1 Following Exposure To Afgf Andmentioning
confidence: 99%